Teaching in Flexible Spatial and Digital Conditions: Re-evaluating Teaching Designs in a Synergi between Space, Actors and Resources - Sofkova Hashemi, Sylvana; Hipkiss, Anna Maria (Educare, 2022)
This study explores the opportunities and challenges of teaching under flexible spatial and digital conditions of the learning environment of a newly build school analyzing how teaching is organized and what curricular genres can be discerned, what resources and practices are offered to stimulate students meaning-making and what framing, relations and accessibility can be discerned in the flexibility of furniture and classroom space. The analyses of one teacher team’s planning and teaching of the thematic work project on Space in years 2-3 (8-9 old children) reveals varied teaching strategies between teacher-led and student-centered forms offering students linguistic, visual and audiovisual resources to make meaning of shared content via different subjects. Spatial framing allows for free movement or static and focused teaching strategies of rather traditional forms of assignments and assessment. These young students practice reading comprehension, both of written texts and films, that also serves building their knowledge about space, thus engaging in skills discourse in combination with thinking and learning discourse.